Surgical outcome prediction in patients with advanced ovarian cancer using computed tomography scans and intraoperative findings - Ha-Jeong Kim; Chel Hun Choi; Yoo-Young Lee; Tae-Joong Kim; Jeong-Won Lee; Duk-Soo Bae; Byoung-Gie Kim (Elsevier, 2014)
Objective: This study aimed to identify features on preoperative computed tomography (CT) scans that are predictive of suboptimal primary cytoreduction and to evaluate the correlation between CT findings and intraoperative findings in advanced ovarian cancer. Materials and methods: We retrospectively reviewed preoperative CT scans and operative findings from patients with stage III/IV epithelial ovarian cancer who underwent primary cytoreduction between 2003 and 2006. Fourteen criteria were assessed. Clinical data were extracted from medical records. Residual tumors measuring ≥1 cm were considered suboptimal. Results: We retrospectively identified 118 patients who met the study inclusion criteria. The rate of optimal cytoreduction (≤1 cm residual disease) was 40%. On preoperative CT scans, omental extension to the stomach or spleen and inguinal or pelvic lymph nodes >2 cm were predictors of suboptimal cytoreduction on univariate (p = 0.016 and p = 0.028, respectively) and multivariate analysis (p = 0.042 and p = 0.029, respectively). Involvement of both omental extension and inguinal or pelvic lymph nodes had a positive predictive value (PPV) of 100%, a specificity of 100%, and an accuracy of 45.8% in predicting suboptimal cytoreduction. We correlated the preoperative CT findings with the intraoperative findings. There were significant correlations between CT and intraoperative findings of omental extension (p = 0.007), inguinal or pelvic lymph nodes >2 cm (p < 0.001), and large bowel mesentery implants >2 cm (p = 0.001). Conclusion: The combination of omental extension to the stomach or spleen and involvement of inguinal or pelvic lymph nodes in preoperative CT scans is considered predictive of suboptimal cytoreduction. These patients may be more appropriately treated with neoadjuvant chemotherapy followed by surgical cytoreduction.